Предмет: Алгебра,
автор: mikebayeva6
Решите пожалуйста по алгебре
Приложения:
Ответы
Автор ответа:
5
Объяснение:
{ 3х - у = -1
{ -х + 2у = 7
{ у = 1 + 3х
{ -х + 2у = 7
-х + 2 * ( 1 + 3х ) = 7
-х + 2 + 6х = 7
5х + 2 = 7
5х = 7 - 2
5х = 5
х = 5 / 5
х = 1
у = 1 + 3 * 1 = 4
х + у = 1 + 4 = 5
~•~•~•ZLOY_TIGROVSKIY~•~•~•
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: cprihobko
Предмет: Другие предметы,
автор: evelinaevtusenko22
Предмет: История,
автор: katiapro100
Предмет: Математика,
автор: аsedrg124vghd78999